Enantioselective synthesis of allylboronates and allylic alcohols by copper-catalyzed 1,6-boration - Luo, Yunfei; Roy, Iain D.; Madec, Amaël G.E.; Lam, Hon Wai (Wiley-VCH Verlag, 2014)
Chiral secondary allylboronates are obtained in high enantioselectivities by the copper-catalyzed 1,6-boration of electron-deficient dienes with B2(pin)2. The reactions proceed efficiently using catalyst loadings as low as 0.0049 mol%. The allylboronates may be oxidized to the allylic alcohols, and can be used in stereoselective aldehyde allylborations. This process was applied to a concise synthesis of atorvastatin.